# Let z = (-5sqrt(3)/2) + (5/2)i and w = 1 + sqrt(3)i a. Convert z and w to polar form. b. Calculate zw. c....

Let z = (-5sqrt(3)/2) + (5/2)i and w = 1 + sqrt(3)i

a. Convert *z* and *w* to polar form.

b. Calculate *zw*.

c. Calculate (*z* / *w*).

*print*Print*list*Cite

### 1 Answer

We have

`z = -(5sqrt(3))/2 + (5/2)i`, `w = 1 + sqrt(3)i`

a)* the polar form of a complex number consists of the argument and the modulus*. Now,

`arg(z) = pi/2 + tan^(-1)(((5sqrt(3))/2)/(5/2)) = pi/2 + tan^(-1)(sqrt(3))`

`= pi/2 + pi/3 = (5pi)/6`

and `|z| = sqrt(((5sqrt(3))/2)^2 + (5/2)^2) = sqrt(75/4 + 25/4) = sqrt(100/4) = 5`

Also,

`arg(w) = tan^(-1)(sqrt(3)) = pi/3` and `|w| = sqrt(1+sqrt(3)^2) = 2`

b) *When complex numbers are multiplied together, their moduli multiply and their arguments add*.

Since a complex number `u` can be written as

`u = |u|[cos(arg(u)) + isin(arg(u))]`

we have that

`zw = (5 times 2)(cos((5pi)/6 + pi/3) + isin((5pi)/6 + pi/3))`

`= 10cos((7pi)/6) + 10sin((7pi)/6)i` `= -5sqrt(3) -5i`

c) Simlarly

`z/w = (5/2)(cos((5pi)/6 - pi/3) + isin((5pi)/6 - pi/3))`

`= (5/2)cos(pi/2) + (5/2)sin(pi/2)i = 0 + (5/2)i`

**answer**